Avaliação do impacto do acompanhamento farmacoterapêutico a pessoas com hipertensão arterial em um município sul-capixaba : ensaio clínico pragmático - Alencar, Taiana de (2024)
Introduction: Arterial hypertension (AH) is a chronic health condition that may require changes in lifestyle and the use of medication. However, this use is not without risks. In this context, the Pharmacotherapeutic Follow-up Service (FHS) has emerged as a strategy capable of improving the health outcomes of people with AH. However, there are few high-research studies on this subject. Objective: To assess the impact of FAS on the health outcomes of patients with AH in the health care network in the municipality of Alegre/ES. Method: This is an experimental single-blind randomized controlled clinical trial. People with hypertension who met the eligibility criteria (over 18 years of age, with self-reported hypertension, taking medication for hypertension for at least 6 months) were randomized in a 1:1 ratio to the intervention and control groups. They received FAS and usual care, respectively, for a period of 12 months. The study was conducted in the Health Care Network of the municipality of Alegre, Espírito Santo, Brazil, from January 2022 to November 2023. In both groups, primary outcomes (blood pressure and quality of life) and secondary outcomes (knowledge about hypertension, anthropometric profile and clinical examinations) were assessed at three points in time, six months apart. Ethical considerations were observed (CAAE registration number 13586319.6.0000.8151 | Opinion no. 4.732.878). Results: 128 patients were allocated to the intervention group (64) and the control group (64). Statistically significant differences were observed in the intra-group analysis in the intervention group, including SBP (∆ = -9.47 mmHg, p = 0.014), Total Cholesterol (∆ = -18.93 mg/dL, p = 0.001), LDL (∆ = -15.70 mg/dL, p < 0.001), non-HDL cholesterol (∆ = -19.76 mg/dL, p < 0.001) and cardiovascular risk (∆ = -1.82 points, p < 0.001). There was an increase in the score for knowledge about hypertension (∆ = 1.39 points, p < 0.001), an improvement in quality of life in the mental state subdimension (∆ = -2.76 points, p = 0.020) and somatic manifestations (∆ = -1.5 points, p = 0.012). In the control group, it was possible to observe an increase in the score for knowledge about hypertension (∆ = 1.52 points, p = 0.001) and an improvement in the VAS of the EQ5D (∆ = 10.33 points, p = 0.067). In addition, almost all the patients were satisfied or very satisfied with the service provided by the pharmacists. Conclusion: The results show a promising positive impact of FAS on clinical and humanistic parameters, as well as a reduction in cardiovascular risk for negative events over the next ten years. This study was registered with The Brazilian Clinical Trials Registry (ReBEC) under registration number: RBR-4c53f3m.